Sighs and Signs of the Spirit: Pneumatic Christian Scholarship and Education - Asamoah-Gyadu, J. Kwabena (Pneuma, 2024)
This article explores the importance of Spirit-empowered scholarship for theological education. It argues that given the overwhelming presence of Christianity in such non-Western contexts as Africa and the options in these new heartlands of Christianity for theological scholarship and education that accounts for the experience of the Spirit, it is appropriate for theological education to pay attention to these developments. This is imperative for the African context in which Pentecostalism with its emphasis on the experience of the Spirit is influencing virtually every area of Christian life including what is meant by theology and theological education.